Teachers' and parents' perceptions of the social skills of mildly mentally retarded children using a researcher-designed instrument - Tangalin, Angelita L. (1984)
Using a researcher-designed instrument, the study surveyed and identified the social skills of mildly mentally retarded children as perceived by their teachers and parents. It was concluded that the scale was a valid and reliable measure; that the problems pertaining to the MMR which parents and teachers consider most pressing were health conditions, inadequacy in communication and negative behavior; that they perceived similarly that MMR children were capable of performing social skills which other normal children can do at home, in school, and in the community; and teacher and parent-respondents have similar agreements and disagreements as to the capabilities of the MMR.
Thesis (M.Ed)--University of the Philippines, Diliman.
Typescript.
Keywords: Mentally handicapped children; Parents -- Attitudes; Social skills; Teachers -- Attitudes